PENINGKATAN HASIL BELAJAR DENGAN METODE PICTURE AND PICTURE PADA MATERI PECAHAN KELAS II SD MUHAMMADIYAH 9 SURABAYA MASA PANDEMI COVID-19 - Faizal Anas Aditya; Kunti Dian Ayu Afiani; Meirza Nanda Faradita (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
This study aims to find out if there is an increase in student learning outcomes, to find out an increase in student activity, to find out an increase in teacher activity in managing learning using the picture and picture method in class II fraction material at SD Muhammadiyah 9 Surabaya during the covid-19 pandemic. This type of research is Classroom Action Research (CAR) which is carried out in cycle stages including planning, implementation, observation and reflection stages. The subject of this Classroom Action Research is the second grade students of SD Muhammadiyah 9 Surabaya, totaling 34 students. The object of this research is the result of learning in the matter of recognizing fractions. The instruments used in this study were observation sheets and test questions. The research data were analyzed descriptively qualitatively and quantitatively. The indicator of the success of this research is if at least 75% of students have reached the KKM, which is 75 and the average grade has reached the KKM. The results showed an increase. Based on student learning outcomes classically increased by 23%